Serapio, Miguel, Francisco, Enrique y Manuel: Religious Sculptures of Ramos Family - Bonilla Soto, Luis Carlos (2024)
This paper systematizes biographical information of three generations of the Ramos family, Costarican religious sculptors from Cartago and Heredia. In addition, it shows artistic pieces produced in their workshops: initiating with sculptures with signature, and then following with a set of pieces attributed to them, due to their formal characteristics. Methodologically, two lines of inquiry are followed, one of a documentary genealogical nature and another descriptive and analytical of the art pieces registered in the database of the Inventory of Sacred Art and other objects destined for the cult of Curia Metropolitana de San José. At the end of this study, a list of pieces uncertain to attribute is drawn up, which are pointed out to serve as a starting point for future research on this subject.